Reuma.pt/vasculitis - the Portuguese vasculitis registry - Ponte, Cristina (2020)
BACKGROUND: The vasculitides are a group of rare diseases with different manifestations and outcomes. New therapeutic options have led to the need for long-term registries. The Rheumatic Diseases Portuguese Register, Reuma.pt, is a web-based electronic clinical record, created in 2008, which currently includes specific modules for 12 diseases and > 20,000 patients registered from 79 rheumatology centres. On October 2014, a dedicated module for vasculitis was created as part of the European Vasculitis Society collaborative network, enabling prospective collection and central storage of encrypted data from patients with this condition. All Portuguese rheumatology centres were invited to participate. Data regarding demographics, diagnosis, classification criteria, assessment tools, and treatment were collected. We aim to describe the structure of Reuma.pt/vasculitis and characterize the patients registered since its development. RESULTS: A total of 687 patients, with 1945 visits, from 13 centres were registered; mean age was 53.4 ± 19.3 years at last visit and 68.7% were females. The most common diagnoses were Behçet's disease (BD) (42.5%) and giant cell arteritis (GCA) (17.8%). Patients with BD met the International Study Group criteria and the International Criteria for BD in 85.3 and 97.2% of cases, respectively. Within the most common small- and medium-vessel vasculitides registered, median [interquartile range] Birmingham Vasculitis Activity Score (BVAS) at first visit was highest in patients with ANCA-associated vasculitis (AAV) (17.0 [12.0]); there were no differences in the proportion of patients with AAV or polyarteritis nodosa who relapsed (BVAS≥1) or had a major relapse (≥1 major BVAS item) during prospective assessment (p = 1.00, p = 0.479). Biologic treatment was prescribed in 0.8% of patients with GCA, 26.7% of patients with AAV, and 7.6% of patients with BD. There were 34 (4.9%) deaths reported. CONCLUSIONS: Reuma.pt/vasculitis is a bespoke web-based registry adapted for routine care of patients with this form of rare and complex diseases, allowing an efficient data-repository at a national level with the potential to link with other international databases. It facilitates research, trials recruitment, service planning and benchmarking.